Hypoxia response in Arabidopsis roots infected by Plasmodiophora brassicae supports the development of clubroot. Issue 1 (December 2016) - Gravot, Antoine; Richard, Gautier; Lime, Tanguy; Lemarié, Séverine; Jubault, Mélanie; Lariagon, Christine; Lemoine, Jocelyne; Vicente, Jorge; Robert-Seilaniantz, Alexandre; Holdsworth, Michael; Manzanares-Dauleux, Maria
Abstract Background The induction of alcohol fermentation in roots is a plant adaptive response to flooding stress and oxygen deprivation. Available transcriptomic data suggest that fermentation-related genes are also frequently induced in roots infected with gall forming pathogens, but the biological significance of this induction is unclear. In this study, we addressed the role of hypoxia responses in Arabidopsis roots during infection by the clubroot agentPlasmodiophora brassicae . Results The hypoxia-related gene markersPYRUVATE DECARBOXYLASE 1 (PDC1), PYRUVATE DECARBOXYLASE 2 (PDC2) andALCOHOL DEHYDROGENASE 1 (ADH1) were induced during secondary infection by two isolates ofP. brassicae, eH and e2.PDC2 was highly induced as soon as 7 days post inoculation (dpi), i.e., before the development of gall symptoms, and GUS staining revealed thatADH1 induction was localised in infected cortical cells of root galls at 21 dpi. Clubroot symptoms were significantly milder in thepdc1 andpdc2 mutants compared with Col-0, but a null T-DNA insertional mutation ofADH1 did not affect clubroot susceptibility. The Arg/N-end rule pathway of ubiquitin-mediated proteolysis controls oxygen sensing in plants. Mutants of components of this pathway, ate1 ate2 andprt6, that both exhibit constitutive hypoxia responses, showed enhanced clubroot symptoms. In contrast, gall development was reduced in quintuple and sextuple mutants where the activity of all oxygen-sensing Group VII Ethylene Response Factor transcription factors (ERFVIIs) is absent (erfVII andprt6 erfVII ). Conclusions Our data demonstrate that the induction ofPDC1 andPDC2 during the secondary infection of roots byP. brassicae contributes positively to clubroot development, and that this is controlled by oxygen-sensing through ERFVIIs. The absence of any major role ofADH1 in symptom development may also suggest that PDC activity could contribute to the formation of galls through the activation of a PDH bypass.